Pengaruh Biaya Promosi Terhadap Peningkatan Jumlah Peserta Asuransi: Studi Di AJB Bumiputera 1912 Divisi Syariah - Salamudin Salamudin (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2014)
The Influence of Promotion Cost to The Increasing of Number Participants: Study at AJB Bumiputera 1912 Shariah Division. The purpose of this study is to analyze the effect of promotion costs to increase in the number of insurance participants. The analysis technique used is linear regression. The results indicate that there are significant show promotion costs to increase in the number of participants who use the benefits of insurance products Iqro Partner ‘of AJB Bumiputera 1912 Division Sharia. In promotional activities the Joint Life Insurance Company (AJB) Bumiputera 1912 Sharia to attract people is through media advertising and sales activities of the agent, of all existing forms of promotion Joint Life Insurance Company (AJB) prefers Sharia Bumiputera 1912 even most promotional activities performed by private sale (personal selling) DOI:10.15408/aiq.v6i1.1372